Social work in general practice - Gilchrist, Iain C. (1978)
A questionnaire seeking details of working arrangements and problems encountered was circulated to social workers working in general practice. The main difficulties were: insufficient preparation for the scheme, poor communication between general practitioners and social workers, and the inadequate provision of facilities for social workers in practice premises. Most of the respondents had not experienced big difficulties. Two thirds had enjoyed a rewarding professional experience, which is a testimonial to interdisciplinary co-operation.